Screening of Arterial Hypertension in the Republic of Kazakhstan: Advantages, Disadvantages and Ways of Improving. - Aigul Shinbolatova; Maksut Kulzhanov; Altyn Aringazina; Ardak Nurbakhyt (Tehran University of Medical Sciences, 2014)
In the Republic of Kazakhstan, the State screening program for early detection of Arterial Hypertension (AH) and other cardiovascular diseases (CVD) for the target age groups was established in 2008.The results of cross-sectional survey conducted at 8 primary health care facilities of Almaty city and Almaty region of Kazakhstan from September 2012 until May 2013 was used. A multistage sampling approach was used to select patients with diagnosed arterial hypertension between 18 to 64 years of age residing in a city (n=405, 50.6%) or village (n=395, 49.4%). Data collection was done via face-to-face interviews using a semi-structured questionnaire.Rural residents (62.7%) mainly were "no-screened". These patients get treatment in policlinics only in case of serious health problems. At younger ages of 18 and 39 years, AH is diagnosed less often among rural than among urban residents (P